EFFECT OF FASTING AND POSTPRANDIAL BLOOD SAMPLES IN RESULTS ON THYROID FUNCTION TEST AMONG EUTHYROID PEOPLE AND PATIENTS WITH THYROID PROBLEM : A SYSTEMATIC REVIEW - Gunawan Halim, Andre; Kreshnayanti, Clarissa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The normal 24-hour rhythm of circulating TSH has a maximum between the hours of 11 p.m. and 5 a.m., and a minimum between the hours of 5 p.m. and 8 p.m. Secretory pulses occur approximately every two to three hours, and they are interspersed with periods of tonic, non-pulsatile TSH production. Although TSH secretion is pulsatile, relatively minor circulatory fluctuations are produced as a result due to the low amplitude of the pulses and the prolonged half-life of TSH. In most cases, the TSH levels taken first thing in the morning during fasting situations are found to be much greater than those obtained later in the same day. When compared to the postprandial blood samples, the TSH result value for the usage of blood samples taken while the patient was fasting would be much greater. As a result, this could be useful in the introduction of a new guideline to standardize the blood sample status for the TSH test screening and diagnosis. The food-induced increase in circulating somatostatin and consequent suppression of TSH levels is one idea that may help to explain the acute postprandial decline in serum TSH levels. Varying increases in plasma somatostatin-14 and somatostatin-28, the two primary bioactive forms, have been recorded in normal volunteers after liquid and solid test meals, with the peak occurring 90–120 minutes after ingestion, likely reflecting somatostatin release from the stomach.